Management of sucking pests in castor with newer insecticides: Management of sucking pests in castor with newer insecticides - P A SARAVANAN; V RAVICHANDRAN; P VEERAMANI; P ARUTCHENTHIL; S R VENKATACHALAM; S MANICKAM; P DURAIMURUGAN (Journal of Oilseeds Research, 2023)
Newer insecticides were evaluated against major sucking pests viz., leafhopper and whitefly in a field experiment conducted at Tapioca and Castor Research Station, Yethapur, TNAU for two years (2021, 2022) during rabi season using castor hybrid YRCH 1. The treatments Thiacloprid 21.7 SC@1ml/l and Cyantranilprole 10.26 OD @ml/l were found superior and recorded significant control of leafhopper (2.48 leafhopper /3 leaves/plant) and whitefly population (1.00 /3 leaves/plant) respectively. The treatments Cynantraniliprole 10.26 OD and Thiacloprid 21.7 SC spray resulted in significantly higher seed yield 1568 kg/ha and 1542kg/ha respectively.